Risk factors for post-thyroidectomy haemorrhage: a meta-analysis. Issue 5 (May 2017) - Liu, Jinhao; Sun, Wei; Dong, Wenwu; Wang, Zhihong; Zhang, Ping; Zhang, Ting; Zhang, Hao
Abstract : Background: Post-thyroidectomy haemorrhage is a rare but potentially life-threatening and unpredictable complication of thyroid surgery. In this study, we analysed the potential risk factors for the occurrence of post-thyroidectomy haemorrhage. Methods: The PubMed and SCIE databases were comprehensively searched for studies published before June 30, 2016. Studies on patients who underwent an open thyroidectomy with or without neck dissection were included, and RevMan 5.3 software was used to analyse the data. Results: Twenty-five studies and 424 563 patients were included in this meta-analysis, and post-thyroidectomy haemorrhage occurred in 6277 patients (incidence rate = 1.48%). The following variables were associated with an increased risk of post-thyroidectomy haemorrhage: older age (MD = 4.30, 95% CI = 3.09–5.52, P < 0.00001), male sex (OR = 1.73, 95% CI = 1.54–1.94, P < 0.00001), Graves' disease (OR = 1.76, 95% CI = 1.44–2.15, P < 0.00001), antithrombotic agents use (OR = 1.96, 95% CI 1.55–2.49, P < 0.00001), bilateral operation (OR = 1.71, 95% CI = 1.50–1.96, P < 0.00001), neck dissection (OR = 1.53, 95% CI = 1.11–2.11, P = 0.01) and previous thyroid surgery (OR = 1.62, 95% CI = 1.12–2.34, P = 0.01). Malignant tumours (OR = 1.07, 95% CI = 0.89–1.28, P = 0.46) and drainage device use (OR = 1.27, 95% CI = 0.74–2.18, P = 0.4) were not associated with post-thyroidectomy haemorrhage. Conclusion: Our systematic review identified a number of risk factors for post-thyroidectomy haemorrhage, including older age, male sex, Graves' disease, antithrombotic agents use, bilateral operation, neck dissection and previous thyroid surgery. Early control of modifiable risk factors could improve patient outcomes and satisfaction.